1991
DOI: 10.1139/v91-212
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical probes of conformational mobility in liquid crystals. The photochemistry of β-phenyl-4-methoxypropiophenone in the nematic and smectic B phases of CCH-n and OS-nm liquid crystals

Abstract: . Can. J. Chem. 69, 1435 (1991).The photochemistry of P-phenyl-4-methoxypropiophenone (1) in the isotropic and liquid crystalline (nematic and smectic B) phases of trans,trans-4'-alkyl-(l,l'-bicyclohexyl)-4-carbonitrile (CCH-n) and trans-4-alkylcyclohexyl-trans-4'-alkylcyclohexylcarboxylate (0s-nm) mesogens has been investigated using nanosecond laser flash photolysis techniques. Solubility limits of 1 as a function of temperature in the smectic phases have been rigorously determined by 'H NMR spectroscopy, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…12,13 Consequently, they have been employed as excellent probes of supramolecular systems. [14][15][16][17][18][19][20][21] The involvement of charge transfer in the intermolecular quenching of triplet-excited ketones by arenes has been long recognized. [22][23][24][25][26] Detailed studies by Wagner and co-workers on the photoreduction of substituted acetophenones and benzophenones with alkylbenzenes showed that both n,π* and π,π* triplets react with alkylbenzenes predominantly by a ratedetermining charge-transfer complexation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Consequently, they have been employed as excellent probes of supramolecular systems. [14][15][16][17][18][19][20][21] The involvement of charge transfer in the intermolecular quenching of triplet-excited ketones by arenes has been long recognized. [22][23][24][25][26] Detailed studies by Wagner and co-workers on the photoreduction of substituted acetophenones and benzophenones with alkylbenzenes showed that both n,π* and π,π* triplets react with alkylbenzenes predominantly by a ratedetermining charge-transfer complexation.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds for which photophysical properties can be conformationally controlled have the potential to probe how supramolecular structures affect the intramolecular mobility of an incorporated molecule. In this context, β-phenylpropiophenones are particularly interesting in that their triplet lifetimes are limited by the conformation, in which the triplet-excited carbonyl group and the β-phenyl ring are in close proximity. , Consequently, they have been employed as excellent probes of supramolecular systems. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies with derivatives substituted on the β-phenyl ring have established the importance of charge transfer It is noteworthy that novel diastereomeric discrimination in the triplet lifetimes of p -methoxy-β-phenylbutyrophenone has been observed in the solid state (racemic vs pure R or pure S crystals), while no discrimination was observed in solution …”
mentioning
confidence: 99%
“…Examples of these effects are found in time-resolved studies of the dynamics of triplet excited state ketones [354,355,361,362] and in kinetic studies of the allyl-p-dimethylaminobenzenesulphonate quaternization discussed above [357,359,3631. Prior to the development of a full understanding of the ramifications of phase separation phenomena, such complex behaviour was often misinterpreted and ascribed to the reaction of a homogeneously solubilized solute in the smectic phase [359, 361 -3631. Examples of SmB -SmA biphasic reactions are also known [364].…”
Section: Solubility Factors and Phase Separationmentioning
confidence: 99%
“…Generally, the presence of the less-ordered phase will result in a 'dilution' of the effect of the higher ordered phase. This has been illustrated succinctly in studies of the Norrish/Yang Type I1 reaction of aryl alkyl ketones in highly ordered smectic phases [352][353][354][355]3601, where the maximumeffect of liquid crystalline order on product distribution (this is always gauged in relation to results obtained for the isotropic phase of the same mesogen, or a reasonable model solvent) was shown to occur at concentrations at or below the solubility limit of the solute. The magnitude of the effect decreases as the bulk solute concentration increases beyond the solubility limit in the mesophase; this is because an increasing fraction of solute resides (and reacts) in a coexisting, solute-rich isotropic or nematic phase.…”
Section: Solubility Factors and Phase Separationmentioning
confidence: 99%